2021
DOI: 10.1016/j.clay.2021.106010
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium aminoclays as plasmid delivery agents for non-competent Escherichia coli JM109 transformation

Abstract: Magnesium aminoclays were synthesized and used to transform non-competent Escherichia coli JM109 using the exogenous plasmid pUC19. The structure determined for the Mg aminoclays is analogous to 2:1 trioctahedral smectites such as talc, with an approximate composition R 8 Si 8 Mg 6 O 16 (OH) 4 , where R = CH 2 CH 2 NH 2 , morphologically arranged in layered sheets. Mg aminoclays were employed as a cationic vehicle that enabled the passage of plasmids across the cell envelope and led to genetic modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Considering that endocytosis is not performed by E. coli JM109, the form factor of the delivery agent should play an important role in transformation due the requirement of a cell envelope piercing mechanism, which should be promoted by nanoscale needle-like morphologies. In fact, sepiolite and Mg aminoclays, being the usual reported delivery agents capable of promoting transformation of microorganisms, also possess a high aspect ratio between two of their dimensions [74,75], which supports this hypothesis. Moreover, theoretical and experimental studies using high aspect ratio nanomaterials such as vertically aligned carbon nanotubes (CNTs) have suggested that the bending energy stored in the CNTs is a substantial factor for the physical rupture of both Gram-positive and Gram-negative bacteria [76].…”
Section: Magnetic Propertiesmentioning
confidence: 58%
“…Considering that endocytosis is not performed by E. coli JM109, the form factor of the delivery agent should play an important role in transformation due the requirement of a cell envelope piercing mechanism, which should be promoted by nanoscale needle-like morphologies. In fact, sepiolite and Mg aminoclays, being the usual reported delivery agents capable of promoting transformation of microorganisms, also possess a high aspect ratio between two of their dimensions [74,75], which supports this hypothesis. Moreover, theoretical and experimental studies using high aspect ratio nanomaterials such as vertically aligned carbon nanotubes (CNTs) have suggested that the bending energy stored in the CNTs is a substantial factor for the physical rupture of both Gram-positive and Gram-negative bacteria [76].…”
Section: Magnetic Propertiesmentioning
confidence: 58%
“…In the presence of aminoclay (2 mg mL −1 ) the pH of DI water increased to ∼9.8. Moreover, the FT-IR spectrum of aminoclay possesses a peak at 2053 cm −1 , assigned to the ionized –NH 3 + group 46,47 (Fig. S3b, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…In the investigation on the transformation of plasmid pUC19 into non-competent E. coli JM109, the OD600 of E. coli JM109 and spreading time were studied. The OD600 of 1.0 and spread time of 90 s were favorable for the transformation process (Mendes et al, 2021a). In the study of Mendes et al (2021b), 2-pyrrolidinone-functionalized needleshaped magnetic nanoparticles were used to form the complexes with plasmid pUC19 and the translocation of nanoparticle-pUC19 complexes across the cell envelope of E. coli JM109 were promoted by frictional stimulation, leading to a maximum transformation efficiency of 3.1 × 102 CFU/µg plasmid.…”
Section: Transformation Of Pgex-rg-(tag)5 Into E Coli Cellsmentioning
confidence: 99%